Antiviral Properties of Peganum Harmala (Espand) as a Medicinal Plant: A Literature Review - Seemin Dashti (Lorestan University of Medical Sciences, 2021)
Labeled Objective: Peganum Harmala is a traditional multipurpose medicinal plant in Iran, China and other countries of Asia and Africa. This review study intends to identify and report its antiviral properties. To carry out this review article, the articles published by Scopus, PubMed, EMBASE, ScienceDirect, Google Scholar, SID, and Magiran from 2010 to 2020 were searched. The key words included Peganum harmala, viral, and virus. 32 articles were found eligible after screening titles and abstracts. After excluding the articles that met the exclusion criteria, eight studies remained. In these studies, the effects of Peganum harmala on some viruses such as the human immunodeficiency virus, influenza A virus, herpes simplex virus type 2, enterovirus 71, herpes simplex virus type 1, and coxsackie B virus type 3 has been investigated. In all of the studies under review, P. harmala smoke or extract has been introduced as an effective antiviral even compared to other disinfectants. According to these findings, it is recommended to pay attention to the Peganum Harmala in processes of viral infections treatments and environmental viral disinfection